Turning Points, Crises, Evolutions - Bałus, Wojciech (Artium Quaestiones, 2019)
When Aristotle asked at what particular moment we can say that an army is fleeing, which is certainly not when individual soldiers start leaving the battlefield, he formulated a problem that is important also for today’s art history: are there any moments in the history of art that can be called turning points? In individual artistic careers, such points are related to crises, allowing the artist to overcome an impasse and find a way toward reaching a goal. Quite often, such a turn occurs suddenly, at some particular moment which ancient Greeks called the kairos. The changes in art approached en bloc also happen thanks to the background of values and some goal of artistic creation. A turning point may imply overcoming a crisis or a period of decline and decadence – always a state of affairs defined in negative terms. A separate case is definitely a political decree that triggers off a change, which implies violence committed on culture. Finally, in academic art history a turning point may be related not only with a crisis, but also with evolution. It’s perception is relative, but because of that the history of art can be rewritten.